(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
One of the main challenges is students’ self-confidence when competing based on their abilities. The purpose of this research is to determine the picture of student self-confidence. This research uses a quantitative method with a descriptive approach with a survey method. The research subjects consisted of 86 students from the UNM Faculty of Psychology. Data collection was carried out using a questionnaire designed based on Lautter’s self-confidence variable. The data obtained was then analyzed using percentage techniques. The results of the research showed that the self-confidence possessed by students included self-confidence, optimistic attitude, responsible attitude, and statement of purpose. Confidence in one’s abilities was 62.8%, positive signals were 48.8%, goals signals were 52.3%, and responsibility signals were shown from the data at 59.3% in developing public speaking skills. In conclusion, most students show indicators of confidence in speaking in public. The implications of this research can be used by students to increase their self-confidence so that they can support students in speaking in public